Rule of law in a free society - Madhava Menon, N. R.; Madhava Menon, N. R., 1935-; Nehru Centre (New Delhi : Oxford University Press, 2008)
With reference to India; contributed articles.
"Nehru Centre."
Keywords: Rule of law -- India